HAKIKAT MAKNA DAN PENGATURAN KEKERASAN BERBASIS GENDER DALAM PERKEMBANGANNYA DI RANAH HUKUM INTERNASIONAL - Mahadewi, Ni Putu Nadine Sekar; Dewi, Tjokorda Istri Diah Widyantari Pradnya (Kertha Negara : Journal Ilmu Hukum; Vol 12 No 11 (2024), 2025)
This research aims to understand the essence of the meaning of Gender-Based Violence (GBV) in its development in the realm of international law and to explore and examine regulations regarding Gender-Based Violence in the development of international law. This article makes use of normative studies methodologies, taking a statutory regulatory technique, and evaluates the effects qualitatively. In line with the findings, gender-based totally completely violence is defined as an act that motives bodily damage to an person primarily based totally on their gender, psychological and/or sexual suffering. As time and technology develop, GBV has developed into Online Gender-Based Violence, namely acts of violence committed via digital platforms and the internet that cause similar suffering to victims through threats, harassment and misuse of personal data online. Although there are several regulations regarding GBV in international law, one example of such law is the conference at the elimination of All varieties of Discrimination closer to women (CEDAW), there is no binding legal source that specifically regulates Online Gender-Based Violence. This shows the absence of norms in international law regarding online KBG, which demands further attention to the development of appropriate regulations to protect individual rights in the digital era. Keywords: Gender Based Violence, Online Gender Based Violence, International Law, CEDAW